Genome-Wide DNA Methylation and Hydroxymethylation Changes Revealed Epigenetic Regulation of Neuromodulation and Myelination in Yak Hypothalamus - Chai, Zhixin; Wu, Zhijuan; Ji, Qiumei; Wang, Jikun; Wang, Jiabo; Wang, Hui; Zhang, Chengfu; Zhong, Jincheng; Xin, Jinwei (Frontiers in Genetics, 2021)
Both 5-methylcytosine (5mC) and 5-hydroxymethylcytosine (5-hmC) are important epigenetic modifications in neurodevelopment. However, there is little research examining the genome-wide patterns of 5mC and 5hmC in brain regions of animals under natural high-altitude conditions. We used oxidative reduced representation bisulfite sequencing (oxRRBS) to determine the 5mC and 5hmC sites in the brain, brainstem, cerebellum and hypothalamus of yak and cattle. We reported the first map of genome-wide DNA methylation and hydroxymethylation in the brain, brainstem, cerebellum and hypothalamus of yak (living at high-altitudes) and cattle. Overall, we found striking differences in 5mC and 5hmC between the hypothalamus and other brain regions in both yak and cattle. Genome-wide profiling revealed that 5mC level decreased and 5hmC level increased in the hypothalamus than in other regions. Furthermore, we identified differentially methylated regions (DMRs) and differentially hydroxymethylated regions (DhMRs), most of which overlapped with each other. Interestingly, transcriptome results for these brain regions also showed distinctive gene levels in the hypothalamus. Finally, differentially expressed genes (DEGs) regulated by DMRs and DhMRs may play important roles in neuromodulation and myelination. Overall, our results suggested that mediation of 5-mC and 5-hmC on epigenetic regulation may broadly impact the development of hypothalamus and its biological functions.